The State of Myristica Swamp Forests in Southern Western Ghats, India - Butterfly Species Richness as an Indicator - Jose, Joyce; Roby, T. J.; Ramachandran, K. K.; Nair, P. V. (Indian Forester, 2015)
Species richness of butterflies in and around the highly fragmented, threatened and restricted patches of Myristica swamp forests in South Western Ghats, Kerala, India was documented. Eighty species of butterflies belonging to 5 families were recorded from these swamp forests with a land area of less than 1.5 km2 (149.75 ha). Species composition inside and outside the swamps showed above 80% similarity Presence-absence of butterfly species was affected by variations in host plant diversity, % of canopy cover, % of inundated area and % of ground litter cover. Habitat usage studies indicated that while habitat specialists were restricted to larger patches of evergreen forests, habitat generalists were not similarly constrained and formed the bulk of the species. The ecotone area between the swamps and the adjacent matrix had relatively more number of species, except where the ecotone had been disturbed. The increase in the butterfly species diversity at the expense of habitat specialists and the proliferation of generalists is an indicator of cryptic changes in the swamp environment leading to increase in microhabitats and host plants associated with disturbance and call for immediate conservation measures.